2015
DOI: 10.5114/aoms.2015.48145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research Predicting reintubation, prolonged mechanical ventilation and death in post-coronary artery bypass graft surgery: a comparison between artificial neural networks and logistic regression models

Abstract: IntroductionIn coronary artery bypass (CABG) surgery, the common complications are the need for reintubation, prolonged mechanical ventilation (PMV) and death. Thus, a reliable model for the prognostic evaluation of those particular outcomes is a worthwhile pursuit. The existence of such a system would lead to better resource planning, cost reductions and an increased ability to guide preventive strategies. The aim of this study was to compare different methods – logistic regression (LR) and artificial neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The NN model was more accurate and outperformed the LR model in predicting in-hospital mortality for patients in critical care [38] and under mechanical ventilation [39]. In this study, although SVM and NN were both expected to handle complex nonlinear relationships between independent and dependent variables better than LR [40,41], the SVM outperformed the NN in the test dataset, and there was no significant difference in AUC values between the LR and SVM. The performance of an ANN depends on the number of parameters, network weights, the selection of an appropriate training algorithm, the type of transfer functions used, and the determination of network size [42].…”
Section: Discussionmentioning
confidence: 87%
“…The NN model was more accurate and outperformed the LR model in predicting in-hospital mortality for patients in critical care [38] and under mechanical ventilation [39]. In this study, although SVM and NN were both expected to handle complex nonlinear relationships between independent and dependent variables better than LR [40,41], the SVM outperformed the NN in the test dataset, and there was no significant difference in AUC values between the LR and SVM. The performance of an ANN depends on the number of parameters, network weights, the selection of an appropriate training algorithm, the type of transfer functions used, and the determination of network size [42].…”
Section: Discussionmentioning
confidence: 87%
“…Mendes et al [21] found that neural networks did not outperform LR when predicting mortality in patients after coronary artery bypass grafting. Other studies have suggested an advantage from ML methods over LR.…”
Section: Discussionmentioning
confidence: 99%
“…Second, unlike the LR model, the ANN model does not have a recognized model of input variable access and elimination. Third, as a result of their structure, ANN models do not provide any medical explanation pertaining to each independent variable; thus, the hypothesis test methods, confidence intervals, and other issues require additional research [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%